Application of Taguchi method in the optimization of geometric parameters for double pin joint configurations made from glass–epoxy nanoclay laminates. (August 2017) - Singh, Manjeet; Saini, J S; Bhunia, H; Singh, Paramdeep
In the present work, Taguchi method was used for the optimization of geometric parameters for double pin joint configurations. The orthogonal array, the signal-to-noise ratio, and analysis of variance were employed to study the effect of geometric parameters on the bearing strength of the joints. Geometric parameters, i.e. the distance from the free edge of the specimen to the diameter of the first hole (E/D) ratio, width of the specimen to the diameter of the hole (W/D) ratio, the distance between the two holes to the diameter of the hole (P/D) ratio and side width to the diameter of the hole (K/D) ratio were investigated for the serial and parallel hole configurations. The results demonstrate that the E/D ratio is the most significant parameter to increase the bearing strength in both serial and parallel pin joint configurations. Its percentage contribution is about 84.5% and 64.23% in serial and parallel pin joint configurations, respectively. Characteristic curve with Tsai–Wu failure criterion was used for the prediction of the bearing strength in the joints numerically. A good agreement was obtained between experimental results and numerical predictions.